Genetic characterization of minor carp (Labeo gonius) from Indian rivers revealed through mitochondrial ATPase 6/8 and D-loop region analysis: implications for conservation and management - Roy, Suvra; Behera, Bijay Kumar; V. L., Ramya; Rout, Ajay Kumar; Kumar, Vikash; Parida, Pranay Kumar; Jana, Asim Kumar; Das, Pronob; Meena, Dharmendra Kumar; Bhakta, Dibakar; Alam, Absar; Das, Basanta Kumar; et al. (Frontiers in Marine Science, 2024)
India is the habitat of many freshwater fish species that make a significant contribution to endemism. However, the native species population is declining at a very fast rate due to pollution, habitat loss or degradation, new species introduction, hydrologic alterations, and overfishing. The minor carp, Labeo gonius is one of the important fish species in the Indian river systems and holds enormous potential in culture fisheries. Therefore, the precise status of population structure is a prerequisite for the management of the species. In the present study, we assessed the potential of mtDNA ATPase 6/8 and D-loop region as a marker to determine the genetic diversity and phylogeography of Labeo gonius from Indian rivers. We have selected five Indian major rivers for investigation which could represent geographically distant populations of the studied fish. A total of 210 ATPase6/8 sequences (842 bp) and 203 D-loop region sequences (683 bp) of L. gonius belonging to the five Indian major rivers were submitted to NCBI. Results revealed that the ATPase6/8 has 17 haplotypes, 70 polymorphic sites with overall haplotype diversity 0.560±0.036 and nucleotide diversity 0.00347±0.00. Furthermore, D-loop analysis revealed 58 haplotypes, 67 polymorphic sites, overall haplotype diversity 0.954±0.006 and nucleotide diversity 0.01914±0.00. The hierarchical AMOVA analysis indicated that a high proportion of the genetic variation (76.46% and 70.22% for D-loop and ATPase6/8 region, respectively) was attributed by among-population variation under gene pool-1 (considering all the Ganga, Brahmaputra, Teesta, Narmada and Mahanadi stocks as a single pool). Furthermore, in gene pool-2, samples were divided into two groups: Group 1 (Himalayan rivers): Ganga, Brahmaputra, and Teesta, and Group 2 (Peninsular rivers): Narmada and Mahanadi. Genetic variations in the D-loop and ATPase6/8 regions were found among populations within groups at 70.65% and 53.48%, respectively. Haplotype network analysis revealed that there were significant differences in distributions and frequencies. The observed unique haplotypes might be useful for differentiating the stocks. In brief, the present study suggested that D-loop and ATPase6/8 regions are potential markers and represent a significant contribution to the genetic characterization of minor cap L. gonius from Indian major rivers.